2016
DOI: 10.1177/1362361316636756
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural exploration of the everyday social participation of individuals with autism spectrum disorders in Australia and Taiwan: An experience sampling study

Abstract: Individuals with an autism spectrum disorder commonly have limited social participation. This study aimed to examine the similarities and differences of everyday participation among males and females with autism spectrum disorder in Australia and Taiwan, using an experience sampling methodology. A total of 14 Australians (4 males, aged 16-43 years) and 16 Taiwanese (12 males, aged 19-45 years) with autism spectrum disorder who are cognitively able were asked to carry a device which prompted them seven times pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The experience of loneliness and isolation emerges as a consistent theme in current studies of autistic adults'1 well-being and experience of social support and social relationships (Baldwin & Costley, 2016;Causton-Theoharis, Ashby, & Cosier, 2009;Chen, Bundy, Cordier, Chien, & Einfeld, 2017;Griffith, Totsika, Nash, & Hastings, 2012;Milton & Sims, 2016;Müller, Schuler, & Yates, 2008). High degrees of experienced loneliness are reported for autistic adults (Mazurek, 2014) and the prevalence of experienced loneliness is higher for autistic children and adolescents when compared to non-autistic individuals (e.g.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The experience of loneliness and isolation emerges as a consistent theme in current studies of autistic adults'1 well-being and experience of social support and social relationships (Baldwin & Costley, 2016;Causton-Theoharis, Ashby, & Cosier, 2009;Chen, Bundy, Cordier, Chien, & Einfeld, 2017;Griffith, Totsika, Nash, & Hastings, 2012;Milton & Sims, 2016;Müller, Schuler, & Yates, 2008). High degrees of experienced loneliness are reported for autistic adults (Mazurek, 2014) and the prevalence of experienced loneliness is higher for autistic children and adolescents when compared to non-autistic individuals (e.g.…”
Section: Introductionsupporting
confidence: 53%
“…persistent difficulties in social communication and social interaction as well as restrictive, repetitive patterns of behaviour, interest or activities. It has so far been a consistent finding and conclusion that the core characteristics of autism may be risk factors for more limited social networks (Chen et al, 2017;Merkler, 2007) and potentially also loneliness (Lasgaard et al, 2010;Merkler, 2007). However, more information is needed on how autistic adults understand the concept of loneliness and whether the general theoretical understanding of loneliness is adequate for the experience and understanding of autistic adults.…”
Section: Introductionmentioning
confidence: 87%
“…The advantage of ESM is that it is flexible and can allow surveys to be short and straightforward with minimal cognitive burden, unlike responses retrieved from interviews (Hektner et al). ESM has been applied to a range of populations to measure wellbeing, quality of life and social interactions (Chen, Bundy, Cordier, Chien & Einfeld, 2016a;Chen, Bundy, Cordier & Einfeld, 2014;Walz, Nauta & Aan Het Rot, 2014;Whalen, Jamner, Henker, Delfino & Lozano, 2002). Traditionally, ESM was conducted via conventional pen and paper reporting (Csikszentmihalyi & Larson).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about how these cross-cultural and contextual differences may affect the degree of impairment induced by symptoms characteristic for ASD. Chen et al (Chen, Bundy, Cordier, Chien, & Einfeld, 2017) compared everyday social participation of autistic individuals in Australia and Taiwan and reported that with similar ASD severity levels Taiwanese participants were more likely to stay at home compared to Australian participants, suggesting that cultural context may shape the degree of participation in day-to-day activities.…”
Section: ) Differences In Whether Symptoms Results In Clinical Impairmentioning
confidence: 99%